Investigation of damping capacity of shape memory alloys - Muhd Haikal Jawahir Eilyaas (2012)
This study focuses on the investigation of the influencing factors of damping capacity in NiTi shape memory alloy. An extensive study of the effects of frequency, strain amplitude, vibration amplitudes and the damping capacity was done on (a) R-phase NiTi shape memory alloy and (b) annealed martensite NiTi shape memory alloy.